2017
DOI: 10.1055/s-0043-110012
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Pelvic Tilt and Pelvic Rotation in Cup Measurement after THA – An Experimental Study

Abstract: ZUSAMMENFASSUNGZiel Nach Hüft-TEP-Versorgungen ist die korrekte Vermessung der Pfannenstellung in postoperativen Röntgenaufnah-men wichtig für die Qualitätskontrolle. In dieser Studie stellen wir eine neue Methode vor, mit der wir Messungenauigkeiten, die sich durch die Beckenverkippung und -verdrehung ergeben, korrigieren können.Methode In einem experimentellen Ansatz implantierten wir eine Prothesenpfanne in ein Kunststoffbecken und bestimmten die tatsächliche Pfannenstellung in einer CT. Um die Auswirkung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…They concluded that the measurement of the vertical distance between the pubic symphysis and the sacrococcygeal joint was the most accurate estimator; however, we noted that the sacrococcygeal joint was visible in only a small proportion of cases, making this method difficult to apply broadly. Additionally, other proposed methods of estimating tilt require additional input or measurement, such as lateral views [20] or additional data on the angle of the central beam of the X-ray [27], information that may be difficult to obtain and/or is beyond the current standard of care. In our study, we chose landmarks that are much more likely to be visible on standard AP radiographs, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the measurement of the vertical distance between the pubic symphysis and the sacrococcygeal joint was the most accurate estimator; however, we noted that the sacrococcygeal joint was visible in only a small proportion of cases, making this method difficult to apply broadly. Additionally, other proposed methods of estimating tilt require additional input or measurement, such as lateral views [20] or additional data on the angle of the central beam of the X-ray [27], information that may be difficult to obtain and/or is beyond the current standard of care. In our study, we chose landmarks that are much more likely to be visible on standard AP radiographs, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce this effect, we derived a correction formula, which can convert the measured values under different PTs into the actual VA values under the natural pelvis, and it was veri ed to be reliable after comparison with the CT values. Several methods have been described for correcting the error of VA measurementowing to the PT in previous studies [15,21,22]. Some of them used formulae as we did [15,21], while othersmodi edmethods using special techniques, such as normograms [22].However, these methods are relatively complex and cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been described for correcting the error of VA measurementowing to the PT in previous studies [15,21,22]. Some of them used formulae as we did [15,21], while othersmodi edmethods using special techniques, such as normograms [22].However, these methods are relatively complex and cumbersome. In contrast, our method can achieve reliable correction only through a simple equation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Liu et al considered three-motion components in the sagittal, coronal, and transversal plane, Pflugi et al measured acetabular orientation by means of its anteversion and inclination. Assessment of acetabular orientation by means of anteversion and inclination is well known from total hip arthroplasty [22][23][24]. Description of spatial orientation of a 3D object (acetabular cup) using 2 parameters only (anteversion and inclination) is just possible if the object has an axis of symmetry.…”
Section: Discussionmentioning
confidence: 99%